1991
DOI: 10.1111/j.1471-4159.1991.tb06343.x
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Trarisduction Mechanism for the Glutamate Action on Phosphoinositide Metabolism via the Quisqualate Metabotropic Receptor in Rat Brain Synaptoneurosomes: I. External Na+ Requirement

Abstract: The characteristics of the transduction mechanism(s) activated by glutamate (Glu) via the quisqualate metabotropic receptor, as well as by depolarizing agents, to trigger formation of inositol phosphates (IPs) were investigated in 8-day-old rat forebrain synaptoneurosomes. The replacement of external Na+ by various compounds (Li+, Tris+, N-methyl-D-glucamine+, and sucrose) induces an increase in basal accumulation of IPs and depolarizes synaptoneurosome membranes. Under these conditions, Glu- and K(+)-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…We have reported that depolarizing agents stimulate IP accumulation and mask the IP accumulation triggered by EAA (Guiramand et al, 1989). We have also found that a rise in intracellular Ca2+ by itself stimulates IP accumulation in this model.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…We have reported that depolarizing agents stimulate IP accumulation and mask the IP accumulation triggered by EAA (Guiramand et al, 1989). We have also found that a rise in intracellular Ca2+ by itself stimulates IP accumulation in this model.…”
Section: Introductionsupporting
confidence: 68%
“…It appears that the stimulatory action of Hg2+ on phosphoinositide metabolism originates from the depolarization that this ion produces. We and others (Gusovsky et al, 1986;Guiramand et al, 1991a) have demonstrated that paired combinations of depolarizing agents never induce an IP accumulation equivalent to the sum of the two maximal IP responses that each of these two substances elicit separately. In order to confirm that depolarization induced by Hg2+ is responsible for the stimulation of basal IP accumulation, we tested the effects on this metabolism of the combination of Hg2+ and another depolarizing agent (K+ or glutamate).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this case, the synaptoneurosomes, following the 1 -h incorporation with ['Hlinositol, were rinsed and then resuspended in a Krebs-Ringer buffer without Ca", in which they were stimulated. Membrane potentials of synaptoneurosomes were determined using the fluorometric probe DiSCz(5) as explained by Guiramand et al (1991).…”
Section: Methodsmentioning
confidence: 99%
“…The existence of at least one new excitatory amino acid (EAA) receptor of the quisqualate (QA) type coupled to the activation of phosphoinositide metabolism, named the "QA metabotropic receptor," is now well established (Sugiyama et al, 1987;RCcasens et al, 1988; for review, see also Sladeczek et al, 1988; RC- casens et al, 1990~;Schoepp et al, 1990;Watkins et al, 1990;RCcasens and Guiramand, 1991). This QA metabotropic receptor, which has been described in various experimental models, possesses a particular pharmacological profile.…”
mentioning
confidence: 99%